2016
DOI: 10.1016/j.sapharm.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence interventions that target subjects with adherence problems: Systematic review and meta-analysis

Abstract: Background Inadequate medication adherence is a pervasive, under-recognized cause of poor health outcomes. Many intervention trials designed to improve medication adherence have targeted adults with adherence problems. No previous reviews have synthesized the effectiveness of medication adherence interventions focused on subjects with medication adherence difficulties. Objective This systematic review and meta-analysis synthesized findings from medication adherence intervention studies conducted among adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
138
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(148 citation statements)
references
References 108 publications
6
138
0
1
Order By: Relevance
“…The overall mean effect size of 0.300, which was calculated across 108 treatment vs. control comparisons, documents that treatment subjects had significantly better medication adherence outcomes than control subjects. This value was comparable to effect sizes reported in meta-analyses of adherence interventions conducted in general populations ( d = 0.18 to 0.37) [147, 148]; among older adults ( d = 0.33) [149]; adults with coronary artery disease ( d = 0.229) [150]; adults with heart failure ( d = 0.29) [151]; patients with adherence problems ( d = 0.301) [152]; and in targeted populations of underrepresented racial/ethnic groups ( d = 0.211) [153]. …”
Section: Discussionmentioning
confidence: 99%
“…The overall mean effect size of 0.300, which was calculated across 108 treatment vs. control comparisons, documents that treatment subjects had significantly better medication adherence outcomes than control subjects. This value was comparable to effect sizes reported in meta-analyses of adherence interventions conducted in general populations ( d = 0.18 to 0.37) [147, 148]; among older adults ( d = 0.33) [149]; adults with coronary artery disease ( d = 0.229) [150]; adults with heart failure ( d = 0.29) [151]; patients with adherence problems ( d = 0.301) [152]; and in targeted populations of underrepresented racial/ethnic groups ( d = 0.211) [153]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies with high baseline adherence rates face difficulty in showing any positive impact of the intervention due to a ceiling effect. Conn et al [32] showed in a systematic review and meta-analysis that interventions targeting those with medication adherence problems have modest but significant effects on medication-taking behavior. Third, small sample sizes leading to low power limited most identified studies.…”
Section: Discussionmentioning
confidence: 99%
“…Habit-based interventions examine participants’ daily routines and link medication administration to existing habitual behaviors or routine events. A previous meta-analysis reported that habit-based interventions were more effective than other interventions at improving adherence among studies targeting chronically ill patients with poor medication adherence (Conn et al, 2015). Habit-based interventions may also be easily tailored to enhancing other healthy habits, such as diet and exercise, that may influence blood pressure outcomes.…”
Section: Discussionmentioning
confidence: 99%